Understanding the universe an introduction to astronomy. Part 5 : the birth and life of the universe - Filippenko, Alexei V.; Stonebarger, Tamara; Moss, Robert (Superstar teachers, 1998)
Eight lectures in a course which "is designed to provide a non-technical description of modern astronomy, including the structure and evolution of planets, stars, galaxies, and the universe as a whole."